Uso de substratos pós-cultivo de cogumelos de Pleurotus ostreatus (Jacq.) na recuperação da fertilidade de um Luvissolo degradado - Salazar, Jhonatan Rafael Zárate (2022)
Agronomic wastes from the most important crops in Paraíba, Brazilian State, such as sugarcane, pineapple, coconut, and banana are often incorporated into the soil as a cultural practice, but in some situations, they are discarded in the field without defined technical criteria and, even they are eventually burned contributing to the emission of greenhouse gases that contaminate the environment. However, these in natura plant materials can be used as substrates to produce edible mushrooms of the species Pleurotus ostreatus (Jacq.) because it is a productive system capable of biodegrading dry agronomic wastes with high contents of lignin, hemicellulose and cellulose using them. metabolically to produce highly nutritious basidiocarps and, in addition, to return to the environment a biodegraded organic material known as spent mushroom substrate (SMS) that when incorporated into the soil favor microbial activity and can act as soil conditioners improving the attributes physical and chemical properties of degraded soils such as those occurring in the semi-arid region of Paraíba, such as some Luvisol. In this context, the objective of this doctoral thesis, in the first instance, was to carry out the transfer of technology from the P. ostreatus production system to the state of Paraíba, recycling its main agronomic wastes to obtain the SMS and, thus, verify its application in the recovery of degraded soils in the Cariri region of Paraíba through its incorporation in Luvisol. The research was divided into 3 stages, which will be presented in the form of chapters: 1. General bibliographic review of the theoretical and scientific bases in relation to the application of SMS in the soil and its foundations in relation to the circular economy; 2. Evaluation of mineral enrichment of in natura agronomic wastes through solid-state fermentation for mushroom production and obtaining of spent mushroom substrate (SMS); and 3. Identification of the effects of SMS application at different doses under the chemical conditioning of Luvisol fertility. From the observed results, we conclude that there is an enrichment of agronomic residues in natura through the mushroom cultivation and that the application of their spent mushroom substrate (SMS) has a positive effect on the chemical conditioning of the soil in a way that allows us to suggest a new valuation of what we classify as agronomic wastes and to propose that it be considered as a new resource for the cultivation of mushrooms that, in addition to providing nutritious food and favoring family farming, can contribute to the management of lignocellulosic wastes available in the region, returning as a more labile organic material, rich in nutrients and with agricultural potential inserted in an integrated system with a focus on the circular economy (zero waste).